Akibat Hukum Terhadap Anak Hasil Perkawinan Siri Pasca Putusan Mahkamah Konstitusi (Lex Jurnalica, 2014)
AbstractDefinition of marriage siri not expressly provided in the Civil Code and the Law 1 of 1974 on Marriage . Article 2 of Law No. 1 of 1974 on Marriage just describe the sense of legal marriage. Therefore, legally , marriage series certainly has a position and due to the status and position of a child . The issue of how the legal position of unregistered marriages views of Law 1 of 1974 concerning marriage and how the legal effect of the position of children unregistered marriages are reviewed according to Law No. 1 of 1974 on Marriage after the verdict of the Constitutional Court No. 46 / PUU - VIII / 2010? (Case Study: Determination No. 683 / Pdt.P.2011.PA.SBY). The method used is a normative legal research, descriptive research analisitis properties, as well as qualitative data analysis. The results show, that the legal position of unregistered marriages is actually the same as a legal marriage as specified in Article 2 paragraph (1) of Law No. 1 of 1974 on Marriage. However, due to not do the recording of the administration of the wedding series as provided in Article 2 paragraph (2) of Law No. 1 In 1974, the legal position of unregistered marriages , can not be recognized. Second , that the legal consequence of the position of children unregistered marriages when viewed according to Law No. 1 of 1974 on Marriage of which is to make the status and position of a child is not recognized when the child was born before the marriage of his parents registered and legally recognized and recording his own birth made one (1) year after the child is born that has exceeded the time limit of birth registration as defined in Article 27 of Law No. 23 Year 2006 concerning Population Administration. Therefore, in taking notes of his birth , requires the court to make a determination of the child can be recognized status and position so that it becomes the same as the legitimate child as defined in Article 32 paragraph (2) of Law No. 23 Year 2006 concerning Population Administration, which reads: "birth registration deadline beyond 1 (one) year as referred to in paragraph (1), carried out by the determination of the district court ".Keyword: due to the law, kawin siri, constitutional court verdictAbstrakPengertian perkawinan siri tidak diatur secara jelas dalam KUH Perdata dan UU No. 1 Tahun 1974 tentang Perkawinan. Pasal 2 UU No. 1 Tahun 1974 tentang Perkawinan hanya menguraikan pengertian perkawinan yang sah. Oleh karena itu secara hukum, perkawinan siri tentunya memiliki kedudukan dan akibat terhadap status dan kedudukan seorang anak. Permasalahan bagaimana kedudukan hukum nikah siri dilihat dari UU No. 1 Tahun 1974 tentang Perkawinan dan bagaimana akibat hukum nikah siri terhadap kedudukan anak ditinjau menurut UU No. 1 Tahun 1974 tentang Perkawinan pasca putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010?. Metode penelitian yang digunakan adalah penelitian hukum normatif, sifat penelitian bersifat deskriptif analisitis, serta analisa data secara kualitatif. Adapun hasil penelitian menunjukkan, bahwa kedudukan hukum nikah siri sebenarnya adalah sama dengan pernikahan yang sah sebagaimana ditentukan dalam Pasal 2 ayat (1) UU No. 1 Tahun 1974 tentang Perkawinan. Akan tetapi dikarenakan tidak dilakukan pencatatan dari sisi administrasinya terhadap pernikahan siri sebagaimana ditentukan Pasal 2 ayat (2) UU No. 1 Tahun 1974 maka secara hukum kedudukan nikah siri, tidak dapat diakui. Kedua, bahwa secara hukum akibat nikah siri terhadap kedudukan anak apabila ditinjau menurut UU No. 1 Tahun 1974 tentang Perkawinan diantaranya adalah membuat status dan kedudukan seorang anak menjadi tidak diakui dimana anak tersebut lahir sebelum perkawinan kedua orangtuanya tercatat dan diakui secara hukum dan pencatatanAkibat Hukum Terhadap Anak Hasil Perkawinan Siri Pasca Putusan Mahkamah KonstitusiÂ Lex Jurnalica Volume 11 Nomor 2, Agustus 2014 131Â kelahirannya sendiri dilakukan 1 (satu) tahun setelah anak tersebut lahir sehingga telah melampaui batas waktu pencatatan kelahiran sebagaimana ditetapkan dalam Pasal 27 UU No. 23 Tahun 2006 tentang Administrasi Kependudukan. Oleh karena itu dalam melakukan pencatatan kelahirannya, membutuhkan penetapan dari pengadilan untuk membuat anak tersebut dapat diakui status dan kedudukannya sehingga menjadi sama dengan anak yang sah sebagaimana ditentukan dalam Pasal 32 ayat (2) UU No. 23 Tahun 2006 tentang Administrasi Kependudukan yang berbunyi: â€œpencatatan kelahiran yang melampaui batas waktu 1 (satu) tahun sebagaimana dimaksud pada ayat (1), dilaksanakan berdasarkan penetapan pengadilan negeri.â€Kata kunci: akibat hukum, kawin siri, putusan MK